Enhancing The Productivity of an Eruptive Petroleum Well by Reduction of Water Inflows - Evodo, Myrille R. N.; Ngatcha, Dianorré T.; Ntep, François; Kibanya, Noel N. (Journal of Petroleum Research and Studies, 2025)
The issue of water inflows is one of the major concerns in the oil industry. This paper presents studies conducted in 2020 on the X field’s well M.01, which, over the years, encountered challenges related to water inflows, though its initial production had no such issues. The primary objective of this paper is to propose a viable solution to reduce water inflows, thereby maximizing surface oil production in a cost-effective manner. To achieve this, a nodal analysis was conducted to evaluate the well’s performance in terms of liquid flow (water and oil). Production logs were used to identify the new oil saturation zone, where new perforations were made. Finally, an economic assessment was performed using the production decline prediction curve. Confidential data, including completion, reservoir, log, and economic data, were processed using PIPESIM and EXCEL software. According to the results, water inflows in well M.01 were caused by the displacement of the water-oil contact, due to partial penetrations via the water cone phenomenon, which reduced oil flow from 3005.585 STB/d to 241.9834 STB/d. To address this issue, a perforation was made using coiled tubing at the 100% oil saturation zone, and the two levels were isolated using a plug via a slickline. This intervention resulted in an oil flow of 2931.087 STB/d, with a water flow of 325.6764 STB/d. After production optimization using wellhead pressure sensitivity curves and flowline diameter adjustments, oil flow increased to 3872.435 STB/d, and water inflow decreased by 90%. The critical flow rate calculation indicated that production must not exceed 5150 STB/d to avoid a rapid water breakthrough. The project to perforate only in the oil saturation zone for optimal production is projected to remain profitable for 11 years, with a return on investment in 1 year, 7 months, and 8 days.